Rape and ravishment in the literature of medieval England - Saunders, Corinne J., 1963- (Cambridge ; Rochester, NY : D.S. Brewer, 2001)
"This work aims to explore and untangle the theme of rape, and its counterpart ravishment, as they developed within Anglo-French cultural tradition across the thousand years between the disintegration of the classical world and the Renaissance." "Medieval writing proves to be far from silent on these issues: this study traces debate and dialogue across intellectual and literary discourses, to place Middle English literary portrayals of rape and ravishment in the context of shifting legal, theological and medical attitudes. Particular emphasis is given to the distinctive legal history of rape in England, as an increased interest in property blurs notions of rape and abduction, and to the rather different concerns of the Church - virginity, chastity, the individual will, the dangers of lust and desire." "The study then considers the treatment of rape and ravishment in a range of literary genres: in hagiography, female saints are repeatedly threatened with rape; the stories of Lucretia and Helen underpin legendary history; the acts of rape and ravishment challenge and shape chivalric order in romance; otherworldly rapes result in the conception of romance heroes. The final two chapters examine the ways in which Malory and Chaucer write and rewrite rape and ravishment."--Jacket
Introduction: The Contemporary and the Contemporaneous -- 1. Secular Law: Rape and Raptus -- 2. Church: Canon Law, Theology and Popular Teaching -- 3. Threat of Rape: Saintly Women -- 4. Legendary History: Lucretia and Helen of Troy -- 5. Middle English Romance: Structures of Possession -- 6. Malory's Morte Darthur: A Romance Retrospective -- 7. 'A Dede of Men': Chaucer's Narrative of Rape.
Includes bibliographical references (pages 319-336) and index.
Print version record.
JSTOR
Keywords: English literature -- Middle English, 1100-1500 -- History and criticism; Rape in literature; Rape -- Religious aspects -- Christianity -- History -- To 1500.; Christian women saints -- Biography -- History and criticism; Women and literature -- England -- History -- To 1500.; Women -- Crimes against -- History -- To 1500.; Romances, English -- History and criticism; Sex crimes in literature; Women in literature; Hagiography; Littérature anglaise -- 1100-1500 (Moyen anglais) -- Histoire et critique; Viol dans la littérature.; Saintes chrétiennes -- Biographies -- Histoire et critique; Roman courtois anglais -- Histoire et critique; Violence sexuelle dans la littérature.; Femmes dans la littérature.; Hagiographie; hagiographies (works); LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Christian women saints -- Biography; English literature -- Middle English; Hagiography; Rape in literature; Rape -- Religious aspects -- Christianity; Romances, English; Sex crimes in literature; Women and literature; Women -- Crimes against; Women in literature; England; To 1500; Literary criticism; Criticism, interpretation, etc; History; Literary criticism; Critiques littéraires.